Effect of Heating Temperature on Magnetic Properties of Fe3O4 Synthesized by Coprecipitation Method - Puryanti, Dwi (Jurnal Ilmu Fisika, 2020)
The synthesis of Fe3O4 nanoparticles with iron rock raw materials was carried out using a coprecipitation method. Iron rocks were taken from the Surian village, South Solok of West Sumatera. This research was conducted to utilize local materials and produce low cost, varied magnetic materials to be applied to the electric and electronics industries. Iron sand as a base material was obtained by processing the iron rocks through destruction and extraction. Iron sand that has been extracted is reacted with HCL and NH4OH. Furthermore, the PEG-2000 were added as a template to homogenize and inhibit the growth of particles. Heating temperature variation performed to see the effect of temperature on the magnetic properties of the particles. Heating temperature variations were used at 500 ̊C, 600 ̊C, and 700 ̊C. Phase composition of the samples were confirm using X-ray diffraction method. Characterization of magnetic properties carried out using Vibrating Sample Magnetometer (VSM). The results of magnetic properties show that the saturation magnetization decreases with increasing heating temperature in the range of 32.6883 emu/g, 20,1632 emu/g, and 10.4734 emu/g respectively. The value of coercive force, HC obtained in the range of 13,840 A/m – 19,120 A/m. The results show that Fe3O4 can be used as a magnetic recording material.